Sexual and reproductive health communication among Sudanese and Eritrean women: an exploratory study from Brisbane, Australia - Rogers, Claire; Earnest, Jaya (Routledge, 2015)
This exploratory study piloted in Brisbane, Australia, reports on findings from in-depth focus-group discussions conducted with Sudanese and Eritrean women in Brisbane. We investigated and documented their experiences and knowledge of sexual and reproductive health and contraception, and explored their views on sexuality and relationships education within the family environment of minority ethnic communities in Australia. Underpinned by a qualitative psychosocial framework, the study also involved key-informant interviews with health and multicultural not-for-profit sector professionals. Through the knowledge and experiences shared by the participants, the key themes of cultural insensitivity, exclusion and poor communication within the family were highlighted by participants as determining factors in the achievement of sexual and reproductive health and good quality sex and relationships education. Participants proposed recommendations for how minority ethnic communities in Australia can more effectively support and communicate within the family environment to increase their own and their children's knowledge and understanding.